How can temporary work agencies provide more training? - Alexander Spermann (IZA World of Labor, 2016)
Temporary work agencies use training as a recruitment and retention argument when qualified labor is scarce. However, short job assignments present a major obstacle for employers and employees to increase investment in training. As temporary agency workers are mainly low-qualified and often previously unemployed, paid work in combination with training should lead to more sustainable employment. Adjustments in labor market institutions could make the provision of training more attractive for both staffing agencies and temporary agency workers.
Keywords: E24; 330; temporary agency work; training; unemployment; job tenure; labor market institutions